Water Use for Energy Production and Conversion in Hebei Province, China - Li, Xiang; Dong, Donglin; Lin, Gang; Yan, Ruiwen; Li, Shuqian (Frontiers in Energy Research, 2020)
In recent years, with the socio-economic development, energy production and water consumption have been given more and more scientific, political and public concern. Taking Hebei Province, China as an example, this paper performs an in-depth analysis of the energy production and water consumption. In this study, the water withdrawal and water consumption associated with energy production in Hebei Province from 2015 to 2050 were estimated by using the bottom-up Long-range Energy Alternative Planning (LEAP) model, which establishes three scenarios based on three different development models. The results show that the energy production and their associated water requirements would continue to grow at a high speed in the Reference Scenario (REF). The energy production and their associated water withdrawal and water consumption were found to have decreased sharply in the Coordinated Development Scenario (CDS) and the Strong Emission Reduction Scenario (SER) compared to the REF. It shows that industrial restructuring, energy structure optimization and the renewable energy replacement have plaid an important role in energyand water-efficient in CDS and SER. Further coordinated management policy on water and energy should be fully considered to promote the sustainable management of water and energy in Hebei Province.